2014
DOI: 10.1016/j.vascn.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Development of yeast reporter assay for screening specific ligands of retinoic acid and retinoid X receptor subtypes

Abstract: The present assay yeasts may be valuable tools for subtype-specific assessments of unidentified environmental ligand chemicals and receptor-specific pharmaceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 48 publications
(42 reference statements)
3
25
0
Order By: Relevance
“…We also recently showed that NP did not affect Rxrγ mRNA in mouse hippocampal neurons (Litwa et al 2014 ). Similarly, Shiizaki et al ( 2014 ) provided a list of compounds that did not alter Rxrγ gene expression (Shiizaki et al 2014 ). However, there are no relevant data from other researchers to compare with the DDE-stimulated protein levels of RXR receptors observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We also recently showed that NP did not affect Rxrγ mRNA in mouse hippocampal neurons (Litwa et al 2014 ). Similarly, Shiizaki et al ( 2014 ) provided a list of compounds that did not alter Rxrγ gene expression (Shiizaki et al 2014 ). However, there are no relevant data from other researchers to compare with the DDE-stimulated protein levels of RXR receptors observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, effort would be directed toward making the causal linkages-via additional experiments, literature reviews, etc.-between the AO and the KEs that precede it (e.g., Ankley et al, 2009;Kimber et al, 2014). Alternatively, an MIE (e.g., a receptor-ligand interaction) may be well characterized with QSAR models and/or in vitro assays that allow chemicals to be rapidly screened for their affinity to the receptor (e.g., Farmahin et al, 2012;Shiizaki et al, 2014;Zhang et al, 2013). However, the understanding of the toxicological significance of those receptor interactions needs to be established.…”
Section: Aop Development Strategiesmentioning
confidence: 99%
“…Moreover, TBT is not only a PPARγ agonist, but also is an agonist for retinoid X receptors (RXR) α and β (le Maire et al 2009; Shiizaki et al 2014). The dual ligand nature of the organotins raises the possibility that RXR could contribute to TBT-induced effects on MSC differentiation, independently of PPARγ.…”
Section: Introductionmentioning
confidence: 99%